2016
DOI: 10.4103/1817-1745.193364
|View full text |Cite
|
Sign up to set email alerts
|

Heart-type fatty acid-binding protein as a predictor of cardiac ischemia in intractable seizures in children

Abstract: Background:Children with intractable epilepsy have chronic dysfunction of the autonomic nervous system causing myocardial ischemia. Heart-type fatty acid-binding protein (H-FABP) is a sensitive biomarker for myocardial ischemia.Aims:We aimed to evaluate serum levels of H-FABP during seizures compared to their interictal levels and healthy controls and changes in heart rate (HR) and HR variability (HRV) in epileptic children with intractable seizures.Materials and Methods:We included 30 epileptic seizures in 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Most have reported trends indicating a shift toward sympathetic dominance, although some failed to find statistically significant differences . In similarly designed studies of pediatric patients, the same patterns are typically seen, although children with drug‐resistant epilepsy often have more severe derangements …”
Section: Interictal Hrv Patterns In Different Epilepsy Typesmentioning
confidence: 95%
“…Most have reported trends indicating a shift toward sympathetic dominance, although some failed to find statistically significant differences . In similarly designed studies of pediatric patients, the same patterns are typically seen, although children with drug‐resistant epilepsy often have more severe derangements …”
Section: Interictal Hrv Patterns In Different Epilepsy Typesmentioning
confidence: 95%
“…Clinical and experimental studies have widely demonstrated that brain hypoxia-ischemia can induce seizures or epilepsy [ 16 , 17 , 18 , 19 , 20 ]. However, whether repetitive episodes of severe seizures as well as SE could induce chronic brain or systemic hypoxia-ischemia have been poorly investigated [ 21 , 22 ]. In this regard, one very complete experimental study confirmed the brain-heart connection in a model of SE induced by kainate.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with epilepsy may have troponin I value as high as 5.5 ng/mL and 6.3 ng/mL after generalized or temporal seizures [28,29], indicating some degree of ischemic myocardial injury due to sympathetic overactivity elicited by the generalized seizure [30,31]. An increase in mean serum levels of heart-type fatty acid-binding protein (H-FABP), a sensitive biomarker for myocardial ischemia, has been reported in children with intractable epilepsy either in the ictal or interictal periods [32], while in patients with known CAD myocardial infarction may follow an epileptic convulsive seizure [33].…”
Section: Discussionmentioning
confidence: 99%